‘Speech based English Language learning’ through synchronous and asynchronous learning environments in Higher Education - Iddamalgoda, Sobani (My University, 2011)
The aim of this study   is to investigate the possibility of using speech activities as a trigger for language acquisition in courses that are conducted to help students acquire English for Academic purposes. In doing so it is intended that the outcomes of the study will contribute to the improvement of language acquisition in Sri Lankan universities and also illuminate the potential of e-learning